Independent evaluation of the effectiveness of IsoCal in improving image center accuracy on Varian TrueBeam and Clinac machines - Du, Weiliang; Gao, Song; Jiang, Wei; Kudchadker, Rajat J. (Journal of applied clinical medical physics, 2018)
Modern medical linear accelerators (linacs) are often equipped with image guidance systems that are capable of megavolt (MV), kilovolt (kV), planar, or volumetric imaging. On Varian TrueBeam linacs, the isocenter accuracies of the imaging systems are calibrated with a procedure named IsoCal. On Clinac series linacs from Varian, installation of IsoCal is optional and the effects of IsoCal on the imaging systems can be turned on or off after the IsoCal procedure is performed. In this study, we report on the effectiveness of IsoCal in improving the coincidence of the image centers with the radiation isocenter, using an independent Winston‐Lutz (WL) method to locate the radiation isocenter. A ball‐bearing phantom was imaged with 2D MV, 2D kV, and cone beam computed radiography systems on two TrueBeam and two Clinac machines. Using the same phantom, digital WL tests with 16 combinations of gantry and collimator angles were performed to locate the radiation isocenter. The offsets between the IsoCal‐calibrated image centers and the WL radiation isocenter were found to be within 0.4 mm on the four linacs in this study. When IsoCal was turned off, the maximal offsets of the image centers were greater than 1.0 mm on the two Clinac machines. The method developed in this study can be used as a vendor‐independent quality assurance tool to assess the isocentricity of the image centers and radiation central axes.